Merentasi sempadan yang melewati zaman kumpulan esei sempena persaraan profesor Dato' Dr. Mohammad Redzuan Othman - Mohammad Redzuan Othman; Amer Saifude Ghazali; Zulkanain Abdul Rahman; Rosmadi Fauzi (Penerbit Universiti Malaya, 2018)
History and criticism of Malay literature and politics and government in Malaysia ; festschrift in honor of Dato' Dr. Mohammad Redzuan Othman, an academician in Malaysia